UTILIZATION OF MODERN INSTRUCTIONAL MATERIALS FOR TEACHING BUSINESS SUBJECTS IN SECONDARY SCHOOLS IN ANAMBRA STATE, NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The need to improve the teaching of business subjects necessitated this study to ascertain thelevel of utilization of modern instructional materials for teaching business subject in secondaryschools in Anambra State, Nigeria. One research question guided the study and three nullhypotheses were tested. Descriptive survey research design was adopted and 249 male andfemale business subjects teachers were studied without sampling. A structured questionnairewas used for data collection. The questionnaire was validated by three experts in the field ofbusiness education and measurement and evaluation from the Faculty of Education, NnamdiAzikiwe University, Awka. A total of 249 copies of questionnaire were distributed to therespondents, 241 copies were correctly filled, retrieved and used for data analysis. Datacollected was analyzed using mean and standard deviation to determine the homogeneity of therespondents’ ratings while t-test was used to test the null hypothesesat 0.05 level of significance.Findings revealed that business subjects teachers rarely utilized modern instructional materialsfor teaching business subjects. The findings also showed that school location and gender weresignificant factors on respondents’ ratings of level of utilization of modern instructionalmaterials while years of experience was not a significant factor. The researchers recommendedamong others that business subjects teachers should endeavour to utilize available moderninstructional materials inthe teachingof business subjects to enable students acquire relevantskills and competencies for gainful employment or self-employment.
Keywords: Business Subjects Teachers, Utilization, Modern Instructional Materials